Analisis Hambatan terhadap Kemampuan Berhitung Siswa Kelas 1 Madrasah Ibtidaiyah - Dwi Muazidah; Kholif Fatmawati; Hanif Islahul Adzim; Dian Mustika Anggraini (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
Early numeracy skills are a fundamental component of children’s cognitive development and serve as an important foundation for success in mathematics learning at the elementary level. Difficulties in mastering basic numeracy concepts can affect students’ academic achievement in subsequent learning stages. This study aims to identify the forms of early numeracy difficulties, examine the factors contributing to these difficulties, and describe the strategies used to overcome them among first-grade students at MI Mashlakul Huda Jekulo, Kudus. The study employed a descriptive qualitative approach with a case study design. Data were collected from 20 students, the classroom teacher, and parents through observation, interviews, and documentation. To strengthen the findings, frequency analysis was conducted using SPSS. The results revealed three major types of early numeracy difficulties experienced by students, namely symbolic difficulties (45%), procedural difficulties (35%), and conceptual difficulties (20%). These difficulties were influenced by both internal and external factors. Internal factors included limited ability to recognize and remember number symbols, low concentration, and varying learning readiness. External factors included limited parental assistance during learning activities, inadequate learning support at home, and sociolinguistic barriers that affected students’ understanding of mathematical concepts. To address these challenges, teachers implemented several strategies, including the use of concrete learning media, a bilingual instructional approach, and interactive homework assignments involving parental participation. The study concludes that improving early numeracy skills requires collaboration between schools and families to create a supportive learning environment and enhance students’ mathematical development.